Agresivitas anak jalanan: Adakah peranan self control dan risk taking behavior? - Clarista Yulani; Dyan Evita Santi; Aliffia Ananta (INNER: Journal of Psychological Research, 2023)
Abstract This research was conducted with the aim of knowing the relationship between self-control and risk-taking behavior with aggressiveness in street children in the Save Street Child Community in Sidoarjo. The population in this study was 35 street children in the Save Street Child Sidoarjo Community. The sampling technique in this study was purposive sampling. The measuring tools used in this study are a self-control scale, a risk-taking behavior scale, and an aggressiveness scale. The data analysis technique used in this research is Spearman’s Rho. Based on the data analysis performed, it shows that there is a relationship between self-control and aggressiveness. This means that the higher the self-control, the lower the aggressiveness, and vice versa. This does not apply to risk-taking behavior and aggressiveness. Based on the data analysis conducted, it shows that there is no relationship between risk-taking behavior and aggressiveness This means that high or low risk-taking behavior does not affect the level of aggressiveness. Keywords: Self Control, Risk Taking Behavior, Aggressiveness